PTEN regulates TLR5‐induced intestinal inflammation by controlling Mal/TIRAP recruitment. Issue 1 (4th October 2012) - Choi, Yoon Jeong; Jung, Jane; Chung, Hyo Kyun; Im, Eunok; Rhee, Sang Hoon
Abstract : Defective IL‐10 allele is a risk factor for intestinal inflammation. Indeed, IL‐10 –/– mice are predisposed to spontaneous colitis in the presence of intestinal microbiota, indicating that microbial factors contribute to developing intestinal inflammation. By recognizing flagellin, TLR5 plays a quintessential role in microbial recognition in intestinal epithelial cells. Here, we treated flagellin (1.0 μg/mouse/d) in mouse colon and found that it elicited colonic inflammation in IL‐10 –/– mice, characterized with tissue hypertrophy, inflamed epithelium, and enhanced cytokine production in the colon (MPO, KC, IL‐6; ≥2‐fold; P < 0.05). These inflammatory effects were dramatically inhibited in TLR5 –/– ;IL‐10 –/– mice. Intestinal epithelium specific PTEN deletion significantly attenuated flagellin‐promoted colonic inflammation in IL‐10 –/– mice. As a molecular mechanism that PTEN deletion inhibited TLR5‐elicited responses, we hypothesized that PTEN regulated TLR5‐induced responses by controlling the involvement of Mal in TLR5 engagement. Mal interacted with TLR5 on flagellin, and Mal deficiency inhibited flagellin‐induced responses in intestinal epithelial cells. Similarly, Mal –/– ;IL‐10 –/– mice showed reduced flagellin‐promoted responses. Furthermore, PTEN deletion disrupted Mal‐TLR5 interaction, resulting in diminished TLR5‐induced responses. PTEN deletion impeded Mal localization at the plasma membrane and suppressed Mal‐TLR5 interaction. These results suggest that, by controlling Mal recruitment, PTEN regulates TLR5‐induced inflammatory responses.—Choi, Y. J., Jung, J., Chung, H. K., Im, E., Rhee, S. H. PTEN regulates TLR5‐induced intestinal inflammation by controlling Mal/TIRAP recruitment. FASEB J. 27, 243–254 (2013). www.fasebj.org